A New Portrait of Constitutive Heterochromatin: Lessons from Drosophila melanogaster. Issue 9 (September 2019) - Marsano, René M.; Giordano, Ennio; Messina, Giovanni; Dimitri, Patrizio
Abstract : Constitutive heterochromatin represents a significant portion of eukaryotic genomes, but its functions still need to be elucidated. Even in the most updated genetics and molecular biology textbooks, constitutive heterochromatin is portrayed mainly as the 'silent' component of eukaryotic genomes. However, there may be more complexity to the relationship between heterochromatin and gene expression. In the fruit fly Drosophila melanogaster, a model for heterochromatin studies, about one-third of the genome is heterochromatic and is concentrated in the centric, pericentric, and telomeric regions of the chromosomes. Recent findings indicate that hundreds of D. melanogaster genes can 'live and work' properly within constitutive heterochromatin. The genomic size of these genes is generally larger than that of euchromatic genes and together they account for a significant fraction of the entire constitutive heterochromatin. Thus, this peculiar genome component in spite its ability to induce silencing, has in fact the means for being quite dynamic. A major scope of this review is to revisit the 'dogma of silent heterochromatin'. Highlights: In the most updated genetics and molecular biology textbooks, constitutive heterochromatin is regarded mainly as the silent component of eukaryotic genomes. In D. melanogaster hundreds of transcriptionally active genes can live and work properly within constitutive heterochromatin; a genomic environment with the long-term reputation of being inhospitable to transcription. Because the heterochromatic genes of D. melanogaster are large, a significant portion of constitutive heterochromatin in this model organism appears to be active, even though the absolute number of genes is small (<300 in a population of 14 000). Thus, while constitutive heterochromatin appears condensed, much of it is accessible to transcription, contributing to the phenotype. Dynamic changes in epigenetic regulators, such as HP1, histone modifications, and chromatin remodelers, may play a role in the expression of D. melanogaster heterochromatic genes during cellular differentiation and development.